Problem-Solving Approach By BHABINKAMTIBMAS In Mediation Of Household Problems In Mulyosari Village - Rahman, Ricky; Asnawi, Habib Shulton; Mukhlishin, A; Pradikta, Hervin Yoki (Fakultas Hukum, Universitas Islam Bandung, 2023)
This article analyzes the success of the role of Bhabinkamtibmas in carrying out problem solving efforts in mediating household problems. The purpose of writing this article is the problem solving technique of Bhabinkamtibmas in mediating household problems. In addition, to reveal the obstacles that occur in problem solving techniques when mediating household problems. This type of research is field research, which is a type of field research, which was conducted in Mulyosari Village, West Metro District, Metro City. The field research study was analyzed qualitatively. This research approach was analyzed using a case study approach. The result of her research is the problem solving of Bhabinkamtibmas in mediating household problems which was taken by Aibda Ali Iqbal by taking several steps, including identifying the problem, looking for several alternative solutions, choosing the best solution, implementing the agreed solution, the result of mediation is that both parties take the path peace. While the obstacle in carrying out mediation is the unanimous determination of the husband and wife to still want to divorce. In addition, disputing parties often give up quickly during the mediation process.